2018
DOI: 10.1002/jat.3582
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity with antibody maytansinoid conjugates: A review of preclinical and clinical findings

Abstract: Maytansinoids, the potent cytotoxic derivatives of the alkaloid maytansine are used as payloads in antibody maytansinoid conjugates. This article reviews clinical and preclinical hepatotoxicity observed with antibody maytansinoid conjugates used to treat cancer. Specific aspects of drug distribution, metabolism and excretion that may impact hepatotoxicity are reviewed vis-à-vis the kind of maytansinoid in the conjugate, cleavable or non-cleavable linkers, linker-payload combinations, drug to antibody ratio, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 118 publications
(226 reference statements)
0
17
0
Order By: Relevance
“…DM4 is a thiol-bearing maytansinoid that contains methyl disulfide substitutions at the C3 N-acyl-N-methyl-L-alanyl ester side chain of maytansine, being suitable for monoclonal antibody attachment [ 58 ]. It exerts its anticancer activity by inhibiting tubulin assembly into microtubules and arresting cell cycle in the G2/M phase [ 59 ]. Finally, topoisomerase I inhibitors are also used.…”
Section: Adcs In Gynecological Tumors: Structure and Functionmentioning
confidence: 99%
“…DM4 is a thiol-bearing maytansinoid that contains methyl disulfide substitutions at the C3 N-acyl-N-methyl-L-alanyl ester side chain of maytansine, being suitable for monoclonal antibody attachment [ 58 ]. It exerts its anticancer activity by inhibiting tubulin assembly into microtubules and arresting cell cycle in the G2/M phase [ 59 ]. Finally, topoisomerase I inhibitors are also used.…”
Section: Adcs In Gynecological Tumors: Structure and Functionmentioning
confidence: 99%
“…Metabolites and catabolites of the drug molecule, with or without the linker, may also be detected [206][207][208][209][210][211]. Pharmacokinetic profiling highlights the impact of the DAR [212] and other perfectible parameters on the biological properties of ADCs, notably the rate of drug loss (from deconjugation and instability) and the clearance of the species with different DARs [213].…”
Section: Adc Bioanalyticsmentioning
confidence: 99%
“…Maytansine was first isolated in 1972 from the plant Maytenus ovatus [1] and showed potent cytotoxic effects in cell-based systems and efficacy in animal tumor models by binding to tubulin and blocking microtubule assembly [1][2][3][4][5]. However, maytansine failed as an anticancer drug in human clinical trials because of its unacceptable systemic toxicity [5][6][7]. Many maytansinoids, chemical derivatives of maytansine, showed higher cytotoxicity-by 100-1000 times-than other tubulin inhibitors, vincristine and vinblastine, in cancer cell lines in vitro [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, maytansine failed as an anticancer drug in human clinical trials because of its unacceptable systemic toxicity [5][6][7]. Many maytansinoids, chemical derivatives of maytansine, showed higher cytotoxicity-by 100-1000 times-than other tubulin inhibitors, vincristine and vinblastine, in cancer cell lines in vitro [7,8]. The structure-antitumor activity relationship revealed that the ester side chain of maytansine plays an important role in the anti-tumor activity as well as tubulin binding [8].…”
Section: Introductionmentioning
confidence: 99%